Percursos de inserção profissional: um estudo com egressos da licenciatura em música da UERN - Costa, Anne Valeska Lopes de (2020)
The current research has, as its main objective, to investigate the paths of professional insertion of the graduates of UERN’s Music Course, and, as specific objectives, to characterize UERN’s graduates in Music, to unveil the trajectory of professional insertion of the graduates in Music of UERN and to identify the paths of insertion of such graduates. Based on the ideas of authors who see professional insertion as a process that has beginning, middle and end (VINCENS, 1997; VERNIÉRES, 1997; ALVES, 2009), I understand, in this study, as professional insertion, the transition from an initial state to a final state, being the initial state the opportunity to obtain any paid activity in the music area, and the final state the opportunity to get a job with an absolutely stable contractual relationship or a situation of relative stability in the world of work. In this work, I tried to answer the following questions: What are the paths of professional insertion of the graduates of UERN’s Music Course? How did the integration of such graduates take place in the world of work? The research method used was the intersectional survey. Online questionnaires were applied with the graduates of UERN’s Music Course, using the research tool JotForm. The study population is formed by 140 people graduated between the years 2008 and 2018. The data presented here correspond to a sample of 116 graduates, which corresponds to 82.8% of the population. The results show that the graduates of UERN’s Music Course are mostly men, white and brown, from low-income families, who entered the world of work in music before they even graduated, mainly in jobs without stability, but that, after studying Music, the vast majority ascended professionally, obtaining safer jobs, mainly with the bond of public civil servant. In general, three insertion routes were the most common among graduates of UERN’s Music Course before, during and after the conclusion of the course: the early insertion route in an unstable job (44%), the concomitant insertion route in an unstable job (50.8%) and the long-term insertion of graduates in a stable job (25.8%). In addition to these, 9.4% of graduates went through the early insertion route in a stable job, 14.6% through the simultaneous insertion route in a stable job, 11.2% through the rapid insertion route in a stable job, 6. 8% went through the path of stability in instability, 3.4% went through the path of precarious insertion and 14.6% are in the path of exclusion.